2015
DOI: 10.1186/s13638-015-0484-1
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap among actor–sensor–actor communication through load balancing multi-path routing

Abstract: Wireless sensor actor networks (WSANs) consist of a large amount of sensor nodes with low cost and little actor nodes with better processing capabilities. The actor nodes tend to get partitioned due to low actor density in case of economic considerations. So, the communication among actors requires sensor nodes to relay his data to the destination actor which lead to the bottleneck in communication. A high-throughput disjoint multi-path (HTDM) routing scheme is proposed in this paper which allows actor simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…There are a lot of studies belong to this category, Ref. [19] proposed a method which adopts different transmit power to reduce the bit error rate (BER) and delay in adaptive MPSK-based wireless sensor networks. We can also see some related research in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of studies belong to this category, Ref. [19] proposed a method which adopts different transmit power to reduce the bit error rate (BER) and delay in adaptive MPSK-based wireless sensor networks. We can also see some related research in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Then the network load on the routes is balanced by an index by each backbone node to distribute the data traffic equally on the links from source to destination. By simulation results, we have shown that proposed technique reduces the network load [24–29].…”
Section: Discussionmentioning
confidence: 99%
“… (6) When BA reaches S or BN i , the node will verifies P z ( i ) estimated using D , BW, and A n values from D . (7) If S receives multiple BA, then there exist multiple paths to D . S chooses nodes with maximum higher pheromone value for data transmission. (8) The routing table is updated using following conditions If there is no communication between nodes, then the pheromone value of the respective link is zero. If there exists communication between nodes, the initial pheromone value 0.1 is deposited on that link of N i and N i [28, 29] Ti,j=0.1 The pheromone value of that link is positively reinforced for each FA received in BN i . Ti,j=Ti,j+normalΔTij where normalΔTij=0.05 If data is not transferred for finite time T de , the pheromone value of the link is decayed by factor α.…”
Section: Proposed Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-throughput disjoint multi-path (HTDM) [14] operates in two different stages. In the first stage, every sensor node obtains the shortest hop to each actor node.…”
Section: Background and Related Workmentioning
confidence: 99%